EVALUASI KINERJA KEUANGAN PT. BARITO PASIFIC TBK - Wendra Hartono (Fakultas Bisnis UKDW, 2018)
ABSTRACTPublicly-listed oil drilling company named by PT. Batrito Pacific Tbk. (BRPT), is one of the fluctuated price of stock and it has undergone a significant growth in the past three years.This is shown by the company performance and increasing financial report annually. Although there is improvement from company performance and financial report, theprospective investors still need to take into account various thing before buy or invested their money towards shares brpt for a longer period of time or not.This research aimed to evaluate the performance and financial report brpt company in the past three years since 2014 up to2016 where the evaluation was to tremendous advantages for both directly as well as an indirect positive impact on an investment decision for the prospective investors to buy shares brpt or not. Fundamental and technical analysis, five forces porter and the facts about corporation or government policies that occurs during the course the past three years were used in this research to discuss and all that is in a fascinating look is likely to give further .The results ofthis research stated the listed shares BRPT is still really good to be purchased or invested for long term period.ABSTRAKPerusahaan PT. Barito Pasific Tbk. atau BRPT, merupakan salah satu saham yang harganya berfluktuatif dan mengalami pertumbuhan yang cukup signifikan selama tiga tahun terakhir. Hal ini dibuktikan dengan kinerja perusahaan dan laporan keuangan yang setiap tahunnya mengalami peningkatan. Meskipun kinerja dan laporan keuangan yang mengalami peningkatan, para calon investor masih perlu mempertimbangkan berbagai hal sebelum membeli atau menginvestasikan uangnya terhadap saham BRPT untuk jangka panjang atau tidak. Penelitian ini bertujuan untuk mengevaluasi kinerja dan laporan keuangan perusahaan BRPT selama tiga tahun terakhir sejak 2014 sampai dengan 2016 dimana evaluasi ini akan memberikan manfaat baik secara langsung maupun tidak langsung terhadap keputusan investasi bagi para calon investor untuk membeli saham BRPTatau tidak. Penelitian ini menggunakan analisis fundamental, teknikal, five forces Porter dan faktafakta tentang kebijkan-kebijakan perusahaan atau pemerintah yang terjadi selama tiga tahun terakhir untuk didiskusikan dan di telaah lebih lanjut. Hasil penelitian ini menyatakan bahwa saham BRPT masih sangat bagus untuk di beli dan di investasikan untuk jangka waktu yang lama